2010
DOI: 10.1111/j.1540-8191.2009.00958.x
|View full text |Cite
|
Sign up to set email alerts
|

Coronary-Coronary Bypass Grafting to Reduce the Risk of Aortic Atheroembolism

Abstract: Coronary-coronary bypass grafting refers to making anastomoses between two segments of the same coronary artery or between different coronary arteries, and provides less "touch" to the aorta, which is important for the patients with severely atherosclerotic ascending aorta. In this report we represent a case of a patient with extensive atherosclerotic aorta, in whom a saphenous vein graft was placed between the acute marginal and the posterior-descending branches of the right coronary artery during an off-pump… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Angiography showed graft patency one year after revascularization. Possibility of coronary-coronary bypasses grafting off-pump in patients with extensive atherosclerotic aorta was also described by Yalcikaya A. et al and Wan L.F. et al [5].…”
Section: History Of Coronary-coronary Bypass Grafting and Its Reporte...mentioning
confidence: 67%
“…Angiography showed graft patency one year after revascularization. Possibility of coronary-coronary bypasses grafting off-pump in patients with extensive atherosclerotic aorta was also described by Yalcikaya A. et al and Wan L.F. et al [5].…”
Section: History Of Coronary-coronary Bypass Grafting and Its Reporte...mentioning
confidence: 67%
“…Agrifoglio et al [ 82 ] have identified a case in which CABG was performed off-pump and the saphenous vein graft was anastomosed proximally to the left common carotid artery. In addition to these methods, the coronary - coronary bypass is an alternative technique that can be used to bypass isolated atherosclerotic coronary lesions in the presence of PA[ 83 , 84 ]. In hemodynamically unstable patients or in whom aortic manipulation cannot be performed due to severely atherosclerotic aorta, performing CABG with the off-pump technique under CPB support and without application of CC can be a good choice to prevent neurologic complications[ 29 , 30 ].…”
Section: Pa and Cabgmentioning
confidence: 99%